The poems of Sir Francis Hubert - Hubert, Francis, Sir, -1629 (Hong Kong University Press, 1961)
A poet of substance though little noticed, Sir Francis Hubert (1568-1629) embodies in his life and works much of the agitated spirit of his times.His verse Historie of Edward the Second, its strong element of political satire, and its minatory finger wagging at the Queen, earned him her official displeasure. He is one of a host of literary figures, which includes Shakespeare, Marlowe, Drayton, and Daniel, who, disturbed by the power in the hands of royal favourites and the problem of succession to Queen Elizabeth, searched history for the parallels, and employed verse as the most effective ins.